The effect of tool path strategies on cutting temperature and cutting force during pocket milling of AISI H13 - Adesta, Erry Yulian Triblas; Riza, Muhammad; Suprianto, Mohamad Yuhan; Hamidon, R. (Asian Research Publishing Network (ARPN), 2016)
Cutting temperature and cutting force generated during high speed machining operations has been recognized as major factors influence tool performance and workpiece geometry. This paper aims to investigate cutting temperature and cutting force behaviours when contour-in and zigzag tool path strategies applied in high speed end milling process. The experiments were carried out on CNC vertical machining center by involving PVD coated carbide inserts. Cutting speed, feed rate and depth of cut were set to vary. Results obtained indicate that cutting temperatures and cutting forces are high in the initial stage of milling and at the corners region or turning points region. Portion of radial depth of cut with workpiece in combination with the abrupt change of the milling path direction occur particularly in acute internal corners of a pocket leads to rise of cutting temperature and cutting force.